Implementasi Media Pembelajaran Platform Blooket terhadap Pemahaman Pembelajaran Bahasa Arab - Muhammad Fahmi Ardiansyah; Aliwafa Aliwafa; Nur Sjamsuarini Pudji Astutik (Alinea: Jurnal Bahasa, Sastra dan Pengajaran, 2025)
This study aims to examine the effectiveness of the gamified digital quiz platform Blooket in improving the vocabulary retention (mufrodat) of Madrasah Tsanawiyah students. The research is grounded in the issue of low vocabulary retention resulting from conventional teaching methods that are less appealing to digital-native learners. The study employed a quantitative research method with a pre-experimental design using a one-group pre-test and post-test model. Data were collected through written tests administered before and after the treatment, while supporting data were obtained through observations of student activities during the learning process. The test instruments were validated using content validity by experts and measured for reliability through Cronbach’s Alpha/KR-20 to ensure consistency. Data analysis included descriptive statistics to examine changes in student scores and inferential statistics through a paired sample t-test to determine the significance of the improvement. The results revealed that the students’ average score increased from 63.20 on the pre-test to 84.13 on the post-test. The N-Gain score of 0.57 indicates a medium-to-high level of effectiveness. The t-test result showed a significance value of 0.000 < 0.05, confirming a significant difference after the use of Blooket. These findings demonstrate that Blooket’s gamification features—such as real-time competition, points, and repeated practice—create an interactive and enjoyable learning environment that enhances vocabulary retention. Therefore, Blooket is effective as an alternative instructional media for improving Arabic vocabulary retention among students at MTsN 4 Sidoarjo.